2020
DOI: 10.1111/trf.15732
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital transfusion of low titer cold‐stored whole blood through the intraosseous route in a trauma patient with hemorrhagic shock

Abstract: BACKGROUND Damage control resuscitation, avoidance of dilutional coagulopathy, and increased blood component therapy reduce mortality after major trauma hemorrhage. Improved outcomes seen in recent warfare have placed whole blood as the preferred product for resuscitation of severe traumatic hemorrhage. As of 2018, flight physicians of the Israeli Airborne Combat Search and Rescue Unit (ACSRU) treat these patients with low titer cold‐stored O‐positive whole blood (LTCSO+WB). Intraosseous (IO) is the preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We utilized a push‒pull infusion technique with a 60 mL syringe because prior research has demonstrated that pressure rarely exceeds 4000 mmHg with this technique and because this technique is currently used by a variety of prehospital medical teams. 30 , 34 …”
Section: Methodsmentioning
confidence: 99%
“…We utilized a push‒pull infusion technique with a 60 mL syringe because prior research has demonstrated that pressure rarely exceeds 4000 mmHg with this technique and because this technique is currently used by a variety of prehospital medical teams. 30 , 34 …”
Section: Methodsmentioning
confidence: 99%
“…Of the 41 overall eligible studies, 19 articles exclusively included trauma patients. 9,18,24,28,31,[35][36][37]41,42,[45][46][47]49,53,[56][57][58]60 Most of these studies were case reports, followed by 4 retrospective studies and 3 prospective observational studies. Only 4 of the trauma studies reported success rates by IO device, with the highest being 100% success using the FAST1, followed by 97% using the EZ-IO.…”
Section: Io Interventionsmentioning
confidence: 99%
“…Pregnant women, cancer patients, and individuals with an illness that causes anemia often have very important transfusion needs, which complicate a blood crisis because these patients require components or specific blood products. 16 , 17 Patients who have experienced serious injuries from car crashes, 18 when the demand for blood is too high, anemia leads to significant morbidity and mortality. 7 …”
Section: Introductionmentioning
confidence: 99%